Правове регулювання екологічної безпеки туристично-рекреаційної діяльності в Україні - Ільїна, М.В. (Економіка природокористування і охорони довкілля, 2013)
Проаналізовано переваги та недоліки сучасного нормативно-правового гарантування екологічної безпеки у сфері туризму і рекреації, зміст та особливості функціонування механізму підвищення екологічної ефективності сфери. Tourism and recreation in Ukraine have been recognized as industries to advance the national economy and support natural resources conservation. The number of national laws and regional executive legislation reflects the Government’s priority to make tourism as environmentally safe industry. The life is different. The industry causes exhaustion of tourist and natural therapeutic and spa resources. The controlling system on environmental safety of the industry is imperfect, and tourist and sanatorium-and-spa business is far from being environmentally friendly. The conclusion is Ukrainian legislation on environmental safety of tourism and recreation business is imperfect, out of date and has to be revised. The issues like division of power controlling environmental safety and scarcity of finance to carry it out are key challenges for policy makers. The legislation gaps, overlaps and unaccomplished the number of national and regional programs on environmental safety make the business environmentally aggressive and blind to the future. Failure to establish national and regional cadastres of natural tourist and medicinal resources indicates the challenge. Lack of the cadastres prevents progress for the sanatorium-and-spa business and recreational industry in Ukraine. It also causes illegal use of natural remedial resources and indirectly induces pollution of the environment. Rural and green tourism in Ukraine are embryonic and there are no legislation to regulate environmental safety of the business.